Recovery of iron from bauxite residue using advanced separation techniques. (April 2019) - Rai, Suchita; Nimje, M.T.; Chaddha, M.J.; Modak, Sweta; Rao, K.R.; Agnihotri, Anupam
Highlights: Advanced separation techniques used for recovery of iron from bauxite residue. Coal dust, most effective reducer amongst sugar cane bagsse, spent spot lining. Reduction roasting is not a good alternative. Best option is Hydrocyclone & magnetic separation with 70% Fe2 O3 and 80% recovery. Abstract: In the Bayer process, bauxite is digested with sodium hydroxide solution at high temperature and pressure producing alumina and generating the waste known as 'red mud' or 'bauxite residue' in large quantity. After the process, the residue which is alkaline in nature has pH of 10.5–13 and is disposed of in red mud ponds. It contains undigested alumina along with a substantial quantity of iron in it (about 35–55%). Keeping in view, the environmental concerns related to red mud, metal recovery remains one of the promising areas. Iron recovery from the bauxite residue would be an alternative for utilization and remediation of hazardous red mud. Using physical methods, iron-rich bauxite residue can be separated and may be utilized as low-grade iron ore. In the paper, advanced physical recovery techniques such as multistage magnetic separation, use of carbon-containing wastes as reducing agents and separation using hydro cyclone have been discussed. A comprehensive study on % recovery and iron present in the desired fraction has been examined. The processes have been discussed using flow diagrams. Comparison of chemical, particle size analysis and scanning electron microscopy of red mud samples in hydro cyclone studies have been studied. Iron content is raised to 70% Fe2 O3 from 52% Fe2 O3 in the original red mud with the recovery of about 80% by adopting hydro-cyclone and magnetic separation route and this seems to be the most appropriate one. Consequently, this article would be immensely useful in deciding the best implementable method for recovery of iron from the bauxite residue and for better waste management.